High Performance Computing for Computational Science - VECPAR 2008 - David Hutchison, Takeo Kanade, Josef Kittler, Jon M. Kleinberg, Friedemann Mattern, John C. Mitchell, Moni Naor, Oscar Nierstrasz, C. Pandu Rangan, Bernhard Steffen, Madhu Sudan, Demetri Terzopoulos, Doug Tygar, Moshe Y. Vardi, Gerhard Weikum, José M. Laginha M. Palma, Patrick R. Amestoy, Michel Daydé, Marta Mattoso, João Correia Lopes (Springer, 2017)
612 p.